Human Rights Norm Diffusion in Southeast Asia - Stanati Netipatalachoochote; Ronald Holzhacker; Aurelia Colombi Ciacchi (Jember University Press, 2018)
Abstract Civil Society Organizations (CSOs) have played an increasingly vocal role in their struggle to advance both human rights protection and promotion in Southeast Asian countries. Most notably, CSOs have become a more important actor in dealing with human rights issues in particular by virtue of their role in drawing attention to human rights violations. In the case of massive human rights violations happening in Southeast Asia, CSOs pursue various strategies to address and try to end such abuses. Spreading information of human rights violations occurring in each member state to regional peers, and then finding new allies such as international organizations to put pressure back to human rights-violating states, in what is characterized as a dynamic of the boomerang model, one of the prominent strategies CSOs use to relieve human rights violations. Another strategy recently observed involves CSOs reaching out to powerful judicial institutions whose decisions can be legally binding on a violating state. Spreding This paper applies the boomerang model theory to the efforts of CSOs, specifically with respect to their work in helping to end the extrajudicial killing of drug dealers in the Philippines during President Duterte’s tenure, to display how the dynamics of the boomerang model works and what this strategy has achieved in terms of ending the extrajudicial killings. Beyond the boomerang model, this paper further demonstrates the strategy of CSOs in reaching out directly to powerful judicial institutions, in this case the International Criminal Court (ICC). The paper discusses why CSOs pursued this strategy of reaching out to the ICC, bypassing the region’s human rights institution—the ASEAN Intergovernmental Commission on Human Rights (AICHR). Keywords: Civil Society Organizations (CSOs); Extrajudicial Killing in the Philippines; The International Criminal Court (ICC). (A previous version of this paper was presented at the 14th Asian Law Institute (ASLI) Conference hosted by the University of Philippines, College of Law (UP) in 19 May 2017. We would like to thank the commentators and the audience for their questions and comments on the paper.)